Pengaruh Likuiditas, Tangibility dan Non Debt Tax Shield Terhadap Struktur Modal - Cahya sinta sari; Dirvi Surya Abbas; Seleman Hardi Yahawi (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This research was conducted to determine the effect of liquidity, tangibility, and non-debt tax shield on capital structure with institutional ownership as a moderator in manufacturing companies listed on the IDX for the 2017-2021 period. The sample used in this research was selected using a purposive sampling method based on several predetermined criteria and resulted in 12 company samples with 60 observation data. The data analysis method uses panel data regression analysis which is tested using Eviews 12 software. The hypothesis testing method uses a significance level of 5%. The research results show that only the non-debt tax shield variable is proven to have a negative effect on capital structure, while the profitability, liquidity and tangibility variables have no effect on capital structure. Institutional ownership is able to increase the effect of non-debt tax shield on capital structure. Institutional ownership is unable to moderate the influence of profitability, liquidity, tangibility on capital structure.